STUDI PENERAPAN STANDAR ISI PENDIDIKAN DI SD NEGERI LEYANGAN - Zulianti Lisa Kurniawati; Matius Kurniawan; Sri Muji; Kurnia Permata Nur Aisah; Sudjono, Sudjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the gap between educational content standards and the field situation. Several schools still face difficulties in implementing educational content standards due to teachers' challenges in delivering learning materials to students. This potentially has a negative impact on the quality of education provided to students. The purpose of this research is to describe and evaluate the implementation of educational content standards at SD Negeri Leyangan. This research uses a descriptive qualitative approach. The study was conducted at SD Negeri Leyangan from May 6, 2024, to May 17, 2024. The data collection techniques used in this research include interviews, observations, and documentation. The data analysis technique involves systematic steps to identify patterns, findings, and meanings that emerge from the collected data. The stages undertaken are: data preparation, method selection, data management, data analysis, data interpretation, and reporting of results. Based on the analysis conducted by the researcher, several important points were identified: collaboration between teachers, students, and parents is crucial in creating an effective learning environment that supports students' understanding of the learning material. Diverse teaching strategies, active student involvement in learning, acknowledgment of challenges in understanding the material, and support from teachers and parents are key factors in enhancing students' comprehension of the learning material.